Analisis Aktivitas Belajar Siswa pada Pembelajaran Matematika: Studi Observasi di SD Inpres 1 Koya Timur - Rahmalia Ayu Isnaini; Rimba Rahmawati; Nurul Oktavia Ramadani; Sharla Martiza; Zhaima Saputri; Didik Efendi (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2026)
This research aims to analyze student learning activities in Mathematics through observational studies at SD Inpres 1 Koya Timur. Student learning activities are an essential aspect in determining the success of learning, particularly in Mathematics, which requires active student involvement in the processes of thinking, reasoning, and problem-solving. This study uses a qualitative approach with observation methods and a systematic literature review. Data were obtained through observations of fifth-grade students' learning activities during Mathematics lessons, supported by relevant literature analysis. The results show that student learning activities include visual, verbal, writing, mental, and emotional activities. Some students displayed active involvement through activities such as asking questions, answering questions, discussing, and completing assignments; however, there were still students showing passive involvement. Factors influencing student learning activities include the role of the teacher, teaching methods, the use of media and learning materials, the classroom environment, and student characteristics. This research concludes that the student learning activities in Mathematics classes at SD Inpres 1 Koya Timur are categorized as fairly active, but improvements are necessary by implementing student-centered learning strategies to make Mathematics learning more effective and meaningful.